2021
DOI: 10.3390/vaccines9010044
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the Curve of COVID-19 Vaccine Rejection—An International Overview

Abstract: Background: If globally implemented, a safe coronavirus disease 2019 (COVID-19) vaccination program will have broad clinical and socioeconomic benefits. However, individuals who anticipate that the coronavirus vaccine will bring life back to normality may be disappointed, due to the emerging antivaccination attitude within the general population. Methods: We surveyed a sample of adult Polish citizens (n = 1066), and compared it with the data on international COVID-19 vaccine reluctance. Results: In 20 national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 18 publications
6
101
4
1
Order By: Relevance
“…However, the worst results were noted in Turkey and the Czech Republic, where more than 40% of the respondents were against COVID-19 vaccination. These results are very alarming, as they may threaten the inability to develop herd immunity, which is a prerequisite for controlling the epidemic of coronavirus [28].…”
Section: Willingness To Get Vaccinatedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the worst results were noted in Turkey and the Czech Republic, where more than 40% of the respondents were against COVID-19 vaccination. These results are very alarming, as they may threaten the inability to develop herd immunity, which is a prerequisite for controlling the epidemic of coronavirus [28].…”
Section: Willingness To Get Vaccinatedmentioning
confidence: 99%
“…In the study by Feleszko et al, 301 respondents who had refused to be vaccinated were additionally asked what could change their mind, and more than half of them claimed that under no circumstances would their change their mind [28]. However, 17% of them could have been convinced with the presentation of the results of scientific research on vaccine safety, 11% would vaccinate themselves to enter foreign countries which would require that, and 10% would take a vaccine if there would be a high fine (1500 €) for not vaccinating themselves or their children.…”
Section: Factors Influencing Positive Attitudes Towards Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…International surveys have shown that 28% of the general population are COVID-19 vaccine hesitant, with the highest rates in the 25-34 age group and in females [9]. Hesitancy reasons include concerns about safety, lack of effectiveness, and the belief that vaccination is unnecessary [10].…”
Section: Introductionmentioning
confidence: 99%
“…The large-majority of data concerning COVID-19 vaccine uptake has been aggregated from hypothetical vaccine uptake surveys [3,5,6] and while rollout of vaccines has begun worldwide, data on vaccine uptake among different populations remains limited. The initial rollout of COVID-19 vaccines in Israel was characterized by a relatively high vaccine uptake and efficiency in vaccine administration.…”
Section: Introductionmentioning
confidence: 99%